How is a queen born? Autoethnographic notes on a Process of Subjectivation in the face of internalized Homophobia - Oliveira Neto, José da Silva (2024)
Internalized homophobia is a common experience throughout the development of homosexual individuals, and there are many scenarios and mediating elements that contribute to its establishment in our life dynamics. Faced with this problem, this study aimed, through a qualitative and autoethnographic approach, to understand the mediating elements of internalized homophobia in homosexual individuals based on the researcher's experience. The Decolony Studies and Historical-Cultural Psychology of L. S. Vigotski were used as a reference for analysis, which, based on the meanings produced in the researcher's experience as a gay man, signaled that: a) autoethnography is a powerful tool for research in the field of sexual diversity; b) there are factors that can intersect with the development of homosexuals, eventually causing psychological illness; and c) we must investigate the protective factors present in the life history of homosexual individuals in order to strengthen their resistance strategies.